(untitled) (Global Journal of Computer Science and Technology, 2013)
A Cloud is a type of parallel and distributed system consisting of a collection of interconnected and virtualized computers that are dynamically provisioned and presented as one or more unified computing resources based on service-level agreements established through negotiation between the service provider and consumers. C loud Computing refers to both the applications delivered as services over the Internet and the hardware and systems software in the data centres that provide those services (Software as a Service - SaaS). The data center hardware and software is what we will call a Cloud. Fr om the studies of various research papers and works done by various researchers it has been found that the major areas of focus in the field of cloud computing are architecture definitions, security, integration of services on various layers, inclusion of Various network and communication devices being developed rapidly. E -Learning through cloud computing is a promising area for the ease of both faculties and students around the world. The work done in cloud computing based e-Learning is oriented on centralized server and further improvement in this can be done. I n this research, a new distributed architecture is being proposed to provide an opportunity to the learners around the world to use the resources being shared by the faculties and online communication between the faculties and students.